The Effectiveness of Adlerian Therapy for Hwa-Byung in Middle-Aged South Korean Womenψ 한국 중년 여성을 대상으로 한 아들러 화병집단상담의 효과성 연구 - Kim, Eunha; Seo, Jungsun; Paik, Hyeyeong; Sohn, Soohyung (Counseling Psychologist, 2020)
Middle-aged South Korean women are at greater risk of developing hwa-byung (South Korean anger syndrome) as compared to men and women of other age groups. In this study, we developed and evaluated the effectiveness of a group counseling program informed by Adlerian individual psychology. Outcome measures included hwa-byung symptoms, depression, and anxiety. We used a cohort-controlled design that compared an intervention condition (n = 22) and a wait-list control group (n = 16), with a 4-week follow-up. Group comparisons showed statistically significant treatment effects for all three outcome measures, which were maintained at follow-up. Mediational analyses revealed that changes in hwa-byung symptoms and depression were mediated by increased social interest. The findings support the effectiveness of a group Adlerian program for middle-aged South Korean women in alleviating hwa-byung symptoms, depression, and anxiety.
Keywords: Adlerian therapy; effectiveness; Hwa-byung; Korean women; program